2003
DOI: 10.1007/s10227-002-0141-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral Famciclovir for the Suppression of Recurrent Genital Herpes: The Combined Data from Two Randomized Controlled Trials

Abstract: Oral famciclovir 250 mg twice daily is an effective, well-tolerated treatment for the suppression of genital HSV infection in patients with frequent recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…65 A larger study evaluating 250 mg of famciclovir twice a day demonstrated that 70% of those receiving the drug were recurrence free for 1 year, compared with only 20% of patients in the placebo group. 82 Various regimens of the drug (125 mg 3 times a day, 250 mg 3 times a day, and 250 mg twice a day) significantly increase time to first recurrence and percentage of patients remaining recurrence free for 1 year. Results attained with 250 mg of famciclovir twice a day or 3 times a day have been similar.…”
Section: Cst In Genital Herpes Simplexmentioning
confidence: 99%
“…65 A larger study evaluating 250 mg of famciclovir twice a day demonstrated that 70% of those receiving the drug were recurrence free for 1 year, compared with only 20% of patients in the placebo group. 82 Various regimens of the drug (125 mg 3 times a day, 250 mg 3 times a day, and 250 mg twice a day) significantly increase time to first recurrence and percentage of patients remaining recurrence free for 1 year. Results attained with 250 mg of famciclovir twice a day or 3 times a day have been similar.…”
Section: Cst In Genital Herpes Simplexmentioning
confidence: 99%
“…Suppressive therapy can reduce the frequency of symptomatic recurrences and asymptomatic viral shedding. 1,7 Famciclovir (Famvir ® , Novartis Pharmaceuticals Corporation, East Hanover, NJ, USA), a prodrug of the antiviral agent penciclovir, has been shown to be effective as both episodic [8][9][10] and suppressive [11][12][13] treatment of recurrent genital herpes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Tyring et al. demonstrated famciclovir 250 mg twice daily to be an effective, well‐tolerated regimen for suppression of genital herpes among individuals with multiple recurrences (39).…”
Section: Introductionmentioning
confidence: 99%